Discovery of Three 22-Membered Macrolides by Deciphering the Streamlined Genome of Mangrove-Derived Streptomyces sp. HM190 - Ye, Yanghui; Anwar, Nusratgul; Mao, Xuming; Wu, Shihua; Yan, Cen; Zhao, Zhe; Zhang, Ran; Nie, Yanfang; Zhang, Jianwei; Wang, Jidong; Wu, Min (Frontiers in Microbiology, 2020)
Strain HM190, a moderate halophile isolated from rhizosphere soil of the mangrove. The 16S rRNA gene sequence and phylogenetic analysis revealed that strain HM190 belonged to the genus Streptomyces and showed the highest sequence similarity of 99.79% to Streptomyces heilongjiangensis NEAU-W2T. The complete genome of strain HM190 comprised 7762826 bp composing a linear chromosome with 71.97 % of the G+C content. According to the antiSMASH analysis, a total of 30 gene clusters were predicted to be involved in secondary metabolism. 12 out of the 30 biosynthetic gene clusters were responsible for the production of polyketide- and non-ribosome peptide-derived secondary metabolites. The gene cluster 5 was responsible for the macrolide biosynthesis in a strain-specific 126331 bp genomic island belonging to the left-arm region. The combined genomics-metabolomics analysis of the strain led to the discovery of three 22-membered macrolides, including a new compound. Their structures were elucidated by using spectroscopic techniques including high resolution electrospray ionization mass spectroscopy (HRESIMS) and nuclear magnetic resonance (NMR). The absolute configuration of new compound was determined by the X-ray single crystal diffraction analysis. All of the three compounds displayed moderate cytotoxic activities to the different tumor cell lines of HepG2, A549 and HCT116.